Public Hearing Aid Policies in Brazil: Operational Gaps, Replacement Costs, and Data Governance in the Unified Health System (SUS) - Ricardo Ferreira Bento; Mara Edwirges Rocha Gândara; Silvio Pires Penteado (International Archives of Otorhinolaryngology, 2026)
Abstract The Brazilian Unified Health System (SUS, from the Portuguese Sistema Único de Saúde) provides free hearing aids (HAs), including otological evaluation, audiological therapy, audiological exams, and ear molds through authorized centers. In addition to the complexity and high investment costs, there is no centralized government agency to manage these resources, so each authorized center works on its own. On the other hand, HAs providers are independent distributors or subsidiaries driven by profit and key-performance indicators in their best interest. To analyze the operational efficiency of SUS in the provision of HAs and explore potential improvements through digital data governance and optimization of replacement rates through simulations. We accessed national data from 2008 to 2024 through the Ministry of Development, Industry and Foreign Trade (COMEX/MDIC) and SUS's Department of Informatics (DATASUS). We integrated these sources with operational data from Reouvir, a leading SUS-accredited center, to model cost scenarios and identify management inefficiencies. Cases from SUS accounted for an average of 49.9% of Brazil's HA imports (3.48 million units, US$437 million). However, high replacement rates—some exceeding 70%—suggest inefficiencies. Simulations indicate that reducing replacement rates by 5 to 20% could yield annual savings of US$1.23 to 5.15 million or enable an increase of 9,780 to 41,026 new fittings per year, respectively. Despite its robust public policy, SUS lacks performance monitoring to enable suppliers to shape market dynamics. Improved digital governance could enhance cost-efficiency and access.